Ambivalence, relationality, complexity and integration grassroots artistic landscape of Macao S.A.R in the post-retrocession era - Mendes, Carla de Utra (University of Saint Joseph, 2017)
This research intends to analyze how the social, political, economical and cultural transformations of the retrocession of Macao S.A.R. to China influenced the contemporary grassroots artistic production, namely their response to the issue of One Country, Two Systems policy. This transitional state of these places in-between creates a somehow ambivalent situation where some of the core values of identity and heritage are fading away due to the forces of the current development. In this sense, it urges to consider the ways in which artists in the post-retrocession era in their lived experiences, form their own sense of community and consciousness of place, time and belonging and, by doing so, can contribute to the preservation of some of the local and specific characteristics, enhancing the cultural vitality of the region. The growing interest by the artists in the issues of preservation and engagement with the locality, trough memory and history, manifested in ‘alternative’ modes of production, is providing a different model of ‘place making’ and a narrative that contrasts and complements some of the top-down cultural policies. Since the focus of development in these territories has been on the idea of creative industries, entertainment and tourism as possible realities for the pressing economical diversification, these grassroots models, functioning as the ‘second system’ open up complexity, providing different questions and answers to the future of artistic production. Finally, departing from these examples, we analyze the possibility of a new image for these kinds of artistic practices, through their incorporation into the possibility of relational aesthetics ‘with Chinese characteristics’, within the perspective of integration, and as emergent features in the field of contemporary art
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

An Investigation on the Effectiveness of Enhancing Public Relations Through the Use of Facebook by the Public Sector of Macau - Chong, Chan U. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Communication between Chinese and Portuguese communities: case study of Macau - Lai, Chi Kei (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

E-Commerce in the Hospitality Industry: The Online Hotel Booking and Digital Marketing in Macau - Chowdee, Nattiya (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Influencer Industry Development in Macau: Case Study about Social Media Influences in Macau - Madan, Roberto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Movie Censorship – A Legitimate Tool or a Dictatorial Technique - Borges, Rui Carlos Moura (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

O trabalho de recuperação de crianças resgatadas do tráfico humano no Nepal=Recovery work for rescued children from human trafficking in Nepal - Espindola, Marcelo Gonçalves (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Os Índios Potiguara: memória, asilo e poder - Simões, José Manuel (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

Redefining Macau's Film Industry: Case Studies on local Film Marketing & Distribution - Choi Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Rethinking special administrative regions Chinese cultural identities and the role of social media: a case study of Macau - Lou, Lai Chu (University of Saint Joseph, 2015)
Hong Kong and Macau were politically reunified with Mainland China in 1997 and 1999, respectively. These two cities culturally originated from Mainland China, but due to their own colonial experiences, the Chinese cultural identities within Hong Kong, Macau, and Mainland China became different. The nature of Chinese cultural identities within Hong Kong and Macau were hybridized, and they have formed their own Chinese cultural identities with their own peculiarities. The Internet is a popular communication medium and it facilitates cultural communication inside and outside of these three places. The high-speed development of modern technology leads to the variety of services that emerge in the Internet, such as discussion forum, Blog, Facebook, Twitter, etc. These new and open spaces serve as a platform for ordinary people to express themselves in different ways. General observations in the Internet reveal that the discussion on Chinese cultural identity among Hong Kong, Macau, and Mainland China exists. The combination of self-identity and reconstruction of self-cultural identity are happening in these differently colonized places. Some local Chinese people in Macau, and Taiwanese in Taiwan, share this kind of experience as well. Meanings in different issues via different symbols are formed and they can be seen from the photos that circulate in the Internet using threads posted in Blogs or discussion forums. All these kinds of images or contexts become symbols of recognizable identities. Internet use, therefore, has facilitated the cultural communication between Hong Kong, Macau, Mainland China, and Taiwan. It has also intensified the enlightenment of Chinese cultural identity, showing and highlighting in effect the remnants of recognizable traits in these territories that were once colonized by different states. In essence, they may arguably have formed heterogeneous Chinese cultural identities. This study presents the uniqueness of the formation of Macau identity in comparison to Hong Kong, and how different it was from Hong Kong after the end of the colonial period. This ‘awakening process’, it is argued, provides a new perspective for understanding the attendant connotations and evaluations of cultural identities, and the different perspectives used to understand how the Internet is reshaping the social world. The reconstruction of cultural identity is a global issue and cultural hybridity is an essential element for reconstruction of self-cultural identity in the postcolonial period. This study employs postcolonial theory, along with observation, in-depth interview and online data collection and content analysis that were adapted during the course of the research, in order to discuss this phenomenon
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Social media propaganda: a case study on its role in the presidency of Rodrigo Duterte - Rivero, Reuben John Limto Rivero (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Study and Analysis of English Press in Macau: Its Impact and Challenges - Pangan, Cheila Alexis Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Study and analysis of the Macau press in Chinese language - Wong, Hio In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The effects of instagram application on the world of photography - Coteriano, Mónica dos Santos (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The History of Macau’s Portuguese Radio Case study of the first thirty episodes of the programme Frequência Académica - Vidinha, Margarida Sajara (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The Perception of Skirt Wearing and Masculinity in Contemporary Society: A Case Study in São Paulo, Brazil and Shanghai, China - Chan, Jose Manuel Enesoe (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

To what extent social media plays a role in Macao emergency public communication? the Macao case study during Typhoon Hato (2017) - Ng, Ka Man (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph